A method for preparing nano carbon material
By adding nanoparticles to chitosan gel and performing multiple calcination and magnetization treatments, the problem of insufficient specific surface area of nanocarbon materials is solved, and its adsorption performance is significantly improved.
Patent Information
- Application Number
- CN202211742543.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The specific surface area of existing nanocarbon materials is insufficient, which affects its adsorption performance.
A specific proportion of nanoparticles are added to the gel formed by chitosan, and the specific surface area of the nanocarbon material is increased by multiple calcination and magnetization treatments.
The specific surface area and adsorption properties of nanocarbon materials are significantly improved, making their pore size small and their adsorption capabilities strong.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano materials, and particularly relates to a method for preparing a nano carbon material. Background Art
[0002] Porous nanocarbon materials have a strong adsorption effect on organic biomolecules and various pollutants in other domestic and industrial wastewater, and have been valued in the field of environmental protection.
[0003] The applicant's prior patent CN113401889A discloses a nanocarbon material and a preparation method thereof. The nanocarbon material is based on chitosan and is calcined twice to obtain a product with a specific surface area of up to 1300 m 2 / g. In subsequent studies, it was found that the specific surface area of the nanocarbon material needs to be further improved. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a nano-carbon material with a larger specific surface area and better adsorption performance and a preparation method thereof.
[0005] The present invention is based on the previous patent and found that adding a specific proportion of nanoparticles to the chitosan gel can increase the specific surface area in the subsequent calcination process.
[0006] The present invention discloses a method for preparing a nano carbon material, comprising the following steps:
[0007] S01, precursor preparation with dissolved chitosan as the main raw material;
[0008] S02, roasting;
[0009] S03, magnetization;
[0010] S04, secondary roasting.
[0011] In some embodiments of the present invention, in S01, the raw materials for preparing the precursor further include nanoparticles and a thickener.
[0012] In some embodiments of the present invention, in S01, the nanoparticles include at least one type of nanoparticles that produce gas when roasted and one type of nanoparticles that do not produce gas when roasted. Preferably, the nanoparticles that produce gas when roasted are carbonates, and the nanoparticles that do not produce gas when roasted are silicon dioxide.
[0013] In some embodiments of the present invention, in S01, the weight ratio of the nanoparticles that produce gas when calcined to the nanoparticles that do not produce gas when calcined is (1-10):(1-2), preferably (1-7.5):(1-1.5), and further preferably (1.5-2):1.
[0014] In some embodiments of the present invention, in S01, the weight ratio of the chitosan to the nanoparticles is (300-500):(50-100), preferably (350-450):(60-80).
[0015] In some embodiments of the present invention, in S01, the thickener is selected from at least one of cellulose and its derivatives, alkali swelling thickeners, polyurethane thickeners and hydrophobically modified non-polyurethane thickeners, preferably one of cellulose and its derivatives.
[0016] In some embodiments of the present invention, in S01, the chitosan is dissolved in an acidic solution, and preferably the acidic solution is an acetic acid aqueous solution.
[0017] In some embodiments of the present invention, in S02, the temperature is raised to 700-800°C under the protection of a nitrogen atmosphere at a heating rate of 3-5°C / min, and then the calcination is continued for 1.5-2h.
[0018] In some embodiments of the present invention, in S03, under a nitrogen atmosphere, the solution is treated in an alkaline aqueous solution of ferric chloride hexahydrate and ferrous sulfate heptahydrate;
[0019] Preferably, the weight ratio of the solidified material D to ferric chloride hexahydrate and ferrous sulfate heptahydrate is (8-10): (4-6): (1-3);
[0020] Preferably, the pH of the aqueous solution is 10-11;
[0021] Preferably, the treatment is carried out at 60-65°C for 2-3h.
[0022] In some embodiments of the present invention, in S04, the temperature is raised to 550-600°C at a heating rate of 8-10°C / min, and then the calcination is continued for 1.5-2h, and the mixture is cooled to room temperature to obtain the nano-carbon material.
[0023] In some embodiments of the present invention, S01 further includes a step of estimating the viscosity of solutions with different chitosan concentrations based on video image processing:
[0024] S11, using a high-speed CCD camera to obtain the formation process of solution droplets with different chitosan concentrations, and obtain the contour feature data of the droplets;
[0025] S12, performing quantitative analysis on the profile data and establishing a working curve;
[0026] S13, using the working curve to estimate the viscosity of a solution of a specific chitosan concentration;
[0027] Wherein, in S11, the contour feature data includes contour area S, circularity O, rectangularity R, contour width W, contour length H and contour perimeter P;
[0028] In S12, the number of video frames F of the droplet growth period and the last 9 feature sequences are used to establish a set of droplet feature samples, denoted as E i =[F i ,T i0 ,,T i1 ,…,T i8 ], where the contour feature of each frame image is T ij =[W ij ,H ij , W ij , W ij , P ij , S ij , Q ij , R ij ](i=1,2,…,N;j=0,1,…,8); Then, the droplet feature sample Ei and its corresponding solution viscosity Vi are combined to form a sample point, which is recorded as D i =(E i ,V i ); Finally, the feature sequence of all solution sample videos is obtained and combined with the corresponding solution viscosity to obtain a sample set and create a data set, which is recorded as D = {(E1, V1), (E2, V2), ..., (E N ,V N )};
[0029] Then, the random forest feature selection algorithm is used to screen irrelevant and redundant features, and the SSA-SVR soft measurement model is trained and constructed to identify liquid viscosity.
[0030] The viscosity estimation step of solutions with different chitosan concentrations based on video image processing in this embodiment is based on video image processing, and has a fast processing speed and high estimation accuracy. Moreover, the random forest feature selection algorithm can alleviate the problem of excessive input data dimension, reduce the difficulty of training the prediction model, and improve the prediction accuracy.
[0031] Beneficial effects of the present invention:
[0032] 1. The nano-carbon material obtained by the preparation method of the nano-carbon material of the present invention has a small pore size, a large specific surface area and a strong adsorption capacity.
[0033] 2. In the method for preparing the nano-carbon material of the present invention, adding nano-powder particles of a specific proportion and composition protected by a thickener in the precursor preparation stage can significantly improve the specific surface area and adsorption performance of the obtained nano-carbon material. DETAILED DESCRIPTION
[0034] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0035] Unless otherwise specified, the examples and comparative examples are parallel tests with the same components, component contents, preparation steps and preparation parameters.
[0036] The calcium carbonate powder and silicon dioxide powder are commercially available nanometer powders. The average particle size of the calcium carbonate powder is 20-100 nm, and the average particle size of the silicon dioxide powder is 80-120 nm.
[0037] Example 1
[0038] A method for preparing a nano-carbon material comprises the following steps:
[0039] (1) Precursor preparation
[0040] Dissolving chitosan in an acetic acid aqueous solution with a mass fraction of 1 wt%, stirring to obtain a mixed solution A, wherein the mass fraction of chitosan in the mixed solution A is 2 wt%;
[0041] Adding calcium carbonate powder and silicon dioxide powder to a 2wt% carboxymethyl cellulose aqueous solution, stirring, to obtain a mixed solution B, wherein the mass fraction of the calcium carbonate powder in the mixed solution B is 50wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 25wt%;
[0042] Mixing the mixed solution A and the mixed solution B at a weight ratio of 200:1, and freeze-drying under vacuum to obtain a solidified product C;
[0043] (2) Calcination
[0044] The solidified product C was heated to 700°C under nitrogen atmosphere protection at a heating rate of 3°C / min, and then calcined for 2 hours to obtain a solidified product D;
[0045] (3) Magnetization
[0046] After deionization and nitrogen flow for 30 minutes, 5 parts by weight of ferric chloride hexahydrate and 2 parts by weight of ferrous sulfate heptahydrate were dissolved in deionized water, and nitrogen was continuously flowed to obtain a 5% aqueous solution, 9 parts by weight of solid D were added, the pH was adjusted to 10.5, and stirred at 60°C for 3 hours; the above operations were all carried out in a nitrogen atmosphere;
[0047] (4) Secondary calcination
[0048] The solid product was collected, washed, and then heated to 550° C. at a heating rate of 8° C. / min, then continued to be roasted for 1.5 hours, and cooled to room temperature to obtain the nano-carbon material.
[0049] Example 2
[0050] A method for preparing a nano-carbon material comprises the following steps:
[0051] (1) Precursor preparation
[0052] Dissolving chitosan in an acetic acid aqueous solution with a mass fraction of 1 wt%, stirring to obtain a mixed solution A, wherein the mass fraction of chitosan in the mixed solution A is 2 wt%;
[0053] Adding calcium carbonate powder and silicon dioxide powder to a 2wt% carboxymethyl cellulose aqueous solution, stirring, to obtain a mixed solution B, wherein the mass fraction of the calcium carbonate powder in the mixed solution B is 50wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 25wt%;
[0054] Mixing the mixed solution A and the mixed solution B at a weight ratio of 200:1, and freeze-drying under vacuum to obtain a solidified product C;
[0055] (2) Calcination
[0056] The solidified product C was heated to 800°C under nitrogen atmosphere protection at a heating rate of 5°C / min, and then calcined for 1.5 hours to obtain a solidified product D;
[0057] (3) Magnetization
[0058] After deionization and nitrogen flow for 30 minutes, 5 parts by weight of ferric chloride hexahydrate and 2 parts by weight of ferrous sulfate heptahydrate were dissolved in deionized water, and nitrogen was continuously flowed to obtain a 5% aqueous solution, 9 parts by weight of solid D were added, the pH was adjusted to 10.5, and stirred at 60°C for 3 hours; the above operations were all carried out in a nitrogen atmosphere;
[0059] (4) Secondary calcination
[0060] The solid product was collected, washed, and then heated to 600° C. at a heating rate of 10° C. / min, then continued to be roasted for 1.5 hours, and cooled to room temperature to obtain the nano-carbon material.
[0061] Example 3
[0062] A method for preparing a nano-carbon material comprises the following steps:
[0063] (1) Precursor preparation
[0064] Dissolving chitosan in an acetic acid aqueous solution with a mass fraction of 1 wt%, stirring to obtain a mixed solution A, wherein the mass fraction of chitosan in the mixed solution A is 2 wt%;
[0065] Adding calcium carbonate powder and silicon dioxide powder to a 2wt% carboxymethyl cellulose aqueous solution, stirring, to obtain a mixed solution B, wherein the mass fraction of the calcium carbonate powder in the mixed solution B is 50wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 25wt%;
[0066] The mixed solution A and the mixed solution B are mixed at a weight ratio of 200:1, and vacuum freeze-dried to obtain a solidified product C;
[0067] (2) Calcination
[0068] The solidified product C was heated to 700°C under nitrogen atmosphere protection at a heating rate of 3°C / min, and then calcined for 2 hours to obtain a solidified product D;
[0069] (3) Magnetization
[0070] After deionization and nitrogen flow for 30 minutes, 5 parts by weight of ferric chloride hexahydrate and 2 parts by weight of ferrous sulfate heptahydrate were dissolved in deionized water, and nitrogen was continuously flowed to obtain a 5% aqueous solution, 9 parts by weight of solid D was added, the pH was adjusted to 11, and the mixture was stirred at 65°C for 2 hours; the above operations were all carried out in a nitrogen atmosphere;
[0071] (4) Secondary calcination
[0072] The solid product was collected, washed, and then heated to 550° C. at a heating rate of 8° C. / min, then continued to be roasted for 1.5 hours, and cooled to room temperature to obtain the nano-carbon material.
[0073] Example 4
[0074] A method for preparing a nano-carbon material comprises the following steps:
[0075] (1) Precursor preparation
[0076] Dissolving chitosan in an acetic acid aqueous solution with a mass fraction of 1 wt%, stirring to obtain a mixed solution A, wherein the mass fraction of chitosan in the mixed solution A is 2 wt%;
[0077] Adding calcium carbonate powder and silicon dioxide powder to a 2wt% carboxymethyl cellulose aqueous solution, stirring, to obtain a mixed solution B, wherein the mass fraction of the calcium carbonate powder in the mixed solution B is 55wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 20wt%;
[0078] The mixed solution A and the mixed solution B are mixed at a weight ratio of 200:1, and vacuum freeze-dried to obtain a solidified product C;
[0079] (2) Calcination
[0080] The solidified product C was heated to 700°C under nitrogen atmosphere protection at a heating rate of 3°C / min, and then calcined for 2 hours to obtain a solidified product D;
[0081] (3) Magnetization
[0082] After deionization and nitrogen flow for 30 minutes, 5 parts by weight of ferric chloride hexahydrate and 2 parts by weight of ferrous sulfate heptahydrate were dissolved in deionized water, and nitrogen was continuously flowed to obtain a 5% aqueous solution, 9 parts by weight of solid D were added, the pH was adjusted to 10.5, and stirred at 60°C for 3 hours; the above operations were all carried out in a nitrogen atmosphere;
[0083] (4) Secondary calcination
[0084] The solid product was collected, washed, and then heated to 550° C. at a heating rate of 8° C. / min, then continued to be roasted for 1.5 hours, and cooled to room temperature to obtain the nano-carbon material.
[0085] Example 5
[0086] A method for preparing a nano-carbon material comprises the following steps:
[0087] (1) Precursor preparation
[0088] Dissolving chitosan in an acetic acid aqueous solution with a mass fraction of 1 wt%, stirring to obtain a mixed solution A, wherein the mass fraction of chitosan in the mixed solution A is 2 wt%;
[0089] Adding calcium carbonate powder and silicon dioxide powder to a 2wt% carboxymethyl cellulose aqueous solution, stirring, to obtain a mixed solution B, wherein the mass fraction of the calcium carbonate powder in the mixed solution B is 45wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 30wt%;
[0090] The mixed solution A and the mixed solution B are mixed at a weight ratio of 200:1, and vacuum freeze-dried to obtain a solidified product C;
[0091] (2) Calcination
[0092] The solidified product C was heated to 700°C under nitrogen atmosphere protection at a heating rate of 3°C / min, and then calcined for 2 hours to obtain a solidified product D;
[0093] (3) Magnetization
[0094] After deionization and nitrogen flow for 30 minutes, 5 parts by weight of ferric chloride hexahydrate and 2 parts by weight of ferrous sulfate heptahydrate were dissolved in deionized water, and nitrogen was continuously flowed to obtain a 5% aqueous solution, 9 parts by weight of solid D were added, the pH was adjusted to 10.5, and stirred at 60°C for 3 hours; the above operations were all carried out in a nitrogen atmosphere;
[0095] (4) Secondary calcination
[0096] The solid product was collected, washed, and then heated to 550° C. at a heating rate of 8° C. / min, then continued to be roasted for 1.5 hours, and cooled to room temperature to obtain the nano-carbon material.
[0097] Example 6
[0098] A method for preparing a nano-carbon material comprises the following steps:
[0099] (1) Precursor preparation
[0100] Dissolving chitosan in an acetic acid aqueous solution with a mass fraction of 1 wt%, stirring to obtain a mixed solution A, wherein the mass fraction of chitosan in the mixed solution A is 2 wt%;
[0101] Adding calcium carbonate powder and silicon dioxide powder to a 2wt% carboxymethyl cellulose aqueous solution, stirring, to obtain a mixed solution B, wherein the mass fraction of the calcium carbonate powder in the mixed solution B is 70wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 5wt%;
[0102] The mixed solution A and the mixed solution B are mixed at a weight ratio of 200:1, and vacuum freeze-dried to obtain a solidified product C;
[0103] (2) Calcination
[0104] The solidified product C was heated to 700°C under nitrogen atmosphere protection at a heating rate of 3°C / min, and then calcined for 2 hours to obtain a solidified product D;
[0105] (3) Magnetization
[0106] After deionization and nitrogen flow for 30 minutes, 5 parts by weight of ferric chloride hexahydrate and 2 parts by weight of ferrous sulfate heptahydrate were dissolved in deionized water, and nitrogen was continuously flowed to obtain a 5% aqueous solution, 9 parts by weight of solid D were added, the pH was adjusted to 10.5, and stirred at 60°C for 3 hours; the above operations were all carried out in a nitrogen atmosphere;
[0107] (4) Secondary calcination
[0108] The solid product was collected, washed, and then heated to 550° C. at a heating rate of 8° C. / min, then continued to be roasted for 1.5 hours, and cooled to room temperature to obtain the nano-carbon material.
[0109] Example 7
[0110] A method for preparing a nano-carbon material comprises the following steps:
[0111] (1) Precursor preparation
[0112] Dissolving chitosan in an acetic acid aqueous solution with a mass fraction of 1 wt%, stirring to obtain a mixed solution A, wherein the mass fraction of chitosan in the mixed solution A is 2 wt%;
[0113] Adding calcium carbonate powder and silicon dioxide powder to a 2wt% carboxymethyl cellulose aqueous solution, stirring, to obtain a mixed solution B, wherein the mass fraction of the calcium carbonate powder in the mixed solution B is 30wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 45wt%;
[0114] The mixed solution A and the mixed solution B are mixed at a weight ratio of 200:1, and vacuum freeze-dried to obtain a solidified product C;
[0115] (2) Calcination
[0116] The solidified product C was heated to 700°C under nitrogen atmosphere protection at a heating rate of 3°C / min, and then calcined for 2 hours to obtain a solidified product D;
[0117] (3) Magnetization
[0118] After deionization and nitrogen flow for 30 minutes, 5 parts by weight of ferric chloride hexahydrate and 2 parts by weight of ferrous sulfate heptahydrate were dissolved in deionized water, and nitrogen was continuously flowed to obtain a 5% aqueous solution, 9 parts by weight of solid D were added, the pH was adjusted to 10.5, and stirred at 60°C for 3 hours; the above operations were all carried out in a nitrogen atmosphere;
[0119] (4) Secondary calcination
[0120] The solid product was collected, washed, and then heated to 550° C. at a heating rate of 8° C. / min, then continued to be roasted for 1.5 hours, and cooled to room temperature to obtain the nano-carbon material.
[0121] Comparative Example 1
[0122] The difference from Example 1 is that in step (1) of precursor preparation, the mass fraction of the calcium carbonate powder in the mixed solution B is 75%, and no silicon dioxide powder is added.
[0123] Comparative Example 2
[0124] The difference from Example 1 is that in step (1) of precursor preparation, the mass fraction of the silicon dioxide powder in the mixed solution B is 75%, and no calcium carbonate powder is added.
[0125] Comparative Example 3
[0126] The difference from Example 1 is that the same equivalent amount of the calcium carbonate powder and the silicon dioxide powder are directly added to the mixed solution A without going through the step of preparing the mixed solution B.
[0127] Experimental Example Performance Test
[0128] The nano-carbon materials obtained in the examples and comparative examples were used to measure the pore size and specific surface area using a BSD-PS2 nano-material specific surface area and pore size measuring instrument produced by Beijing Best Instrument Technology Co., Ltd.
[0129] The results show that the average pore size of Examples 1-5 is below 20 nm, which is significantly better than that of Comparative Examples 1-3, among which the average pore size of Examples 1-3 is below 15 nm. The specific surface area of Examples 1-5 is above 1100 m 2 / g or more, while the comparative examples 1-3 are at 900m 2 / g or less, wherein Examples 1-3 are all at 1500m 2 / g or above.
[0130] The preferred specific implementation modes and embodiments of the present invention are described in detail above, but the present invention is not limited to the above implementation modes and embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the concept of the present invention.
Claims
1. A method for preparing a nano-carbon material, characterized in that: The following steps are involved: S01, precursor preparation with dissolved chitosan as the main raw material; S02, roasting; S03, magnetization; S04, secondary roasting; In S01, the raw materials for the precursor preparation also include nanoparticles and a thickener; The nanoparticles include at least one type of nanoparticles that generate gas when calcined and one type of nanoparticles that do not generate gas when calcined; In S01, chitosan is dissolved in an acetic acid aqueous solution with a mass fraction of 1 wt%, and stirred to obtain a mixed solution A, wherein the mass fraction of the chitosan in the mixed solution A is 2 wt%; Calcium carbonate powder and silicon dioxide powder are added to a 2wt% carboxymethyl cellulose aqueous solution, and stirred to obtain a mixed solution B, wherein the mass fraction of the calcium carbonate powder in the mixed solution B is 50wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 25wt%; or the mass fraction of the calcium carbonate powder in the mixed solution B is 55wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 20wt%; or the mass fraction of the calcium carbonate powder in the mixed solution B is 45wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 30%; or the mass fraction of the calcium carbonate powder in the mixed solution B is 70wt%, and the mass fraction of the silicon dioxide powder in the mixed solution B is 5wt%; The mixed solution A and the mixed solution B were mixed at a weight ratio of 200:1, and vacuum freeze-dried to obtain a solidified product C.
2. The method for preparing nanocarbon material according to claim 1, characterized in that: In S02, the solidified material C in S01 is heated to 700-800°C under the protection of a nitrogen atmosphere at a heating rate of 3-5°C / min, and then calcined for 1.5-2h.
3. The method for preparing the nanocarbon material according to claim 1 or 2, characterized in that: In S03, the solidified product D obtained by calcining S02 is treated in an alkaline aqueous solution of ferric chloride hexahydrate and ferrous sulfate heptahydrate under a nitrogen atmosphere.
4. The method for preparing nano-carbon material according to claim 3, characterized in that: The weight ratio of the solidified material D to ferric chloride hexahydrate and ferrous sulfate heptahydrate is (8-10): (4-6): (1-3).
5. The method for preparing nano-carbon material according to claim 3, characterized in that: The pH of the aqueous solution is 10-11.
6. The method for preparing nano-carbon material according to claim 3, characterized in that: Treat at 60-65°C for 2-3h.
Citation Information
Patent Citations
Temperature-sensitive chitosan-carboxymethylcellulose gel and preparation method thereof
CN103601898A
Porous hard carbon negative electrode material, preparation method thereof and lithium ion battery
CN108963253A
Nano-carbon material and preparation method thereof
CN113401889A